2015
DOI: 10.1108/ijphm-05-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Trade performance and revealed comparative advantage of Indian pharmaceutical industry in new IPR regime

Abstract: Purpose – The purpose of this paper is to examine the trade performance, revealed comparative advantage and trade specialisation indices of Indian pharmaceutical in the post-modified Indian Patent Act. Design/methodology/approach – The main data sources for this paper are United Nations Conference on Trade and Development, PROWESS of Centre for Monitoring Indian Economy, Government of India reports and Reserve Bank of India databases. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Profitabilit y Liquidity Financial Performan ce property rights) has opportunities and threats to the industry (Mahajan et al, 2015). Overall, the pharmaceutical companies of India are scaling the heights and scoring the enhanced goals of revenue every year, but it does not disclose the insights of the pharmaceuticals companies.…”
Section: Enhanc Esmentioning
confidence: 99%
“…Profitabilit y Liquidity Financial Performan ce property rights) has opportunities and threats to the industry (Mahajan et al, 2015). Overall, the pharmaceutical companies of India are scaling the heights and scoring the enhanced goals of revenue every year, but it does not disclose the insights of the pharmaceuticals companies.…”
Section: Enhanc Esmentioning
confidence: 99%
“…As a result, the pharmaceutical sector of most developing countries except a few is unable to make significant contributions to the global market. For instance, Mahajan et al (2015) demonstrate that the Indian pharmaceutical industry has largely capitalised on its low-cost production of generic drugs. EEPC India (2013) shows that India's pharmaceutical exports were around US$8 billion in 2009, and reached US$19.13 billion in 2019 and then US$20 billion in 2020demonstrating a growth rate of over 30 per cent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also includes expenditure of high cost and time in conducting clinical trials with low success rate in product discovery and clinical development, generic competition at the end of product patent life followed by high uncertainties in demands and capacity planning (Lainez et al, 2012). In the Indian context, Mahajan et al (2015) observed that the pharmaceutical industry has largely capitalized on its low cost production of generic drugs. It includes the internal chain such as patient care units, hospital storage and the external chain such as producers, purchasers and distributors (Mehralian et al, 2012).…”
Section: Background Of the Studymentioning
confidence: 99%